2018
DOI: 10.22159/ajpcr.2018.v11i10.26789
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Blood Hematology in Relation With Maternal Anemia: A Preliminary Study

Abstract: Objectives: The aim of this study was to observe any umbilical cord blood hematological changes in relation to maternal anemia.Methods: We conducted a cross-sectional study on 220 neonates and their mothers from August 1, 2015, to July 31, 2016, in collaboration with the Department of Obstetrics and Gynaecology, Regional Institute of Medical Sciences, Imphal, India. Immediately after vaginal delivery of baby, umbilical cord was clamped and blood was collected in EDTA vials and analyzed using automated hematoan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Furthermore, endemic parasitic infections in these geographic areas, lifestyle and socio-economic conditions could also be associated with high prevalence of anemia (Ayano and Amentie, 2018). These results are similar to those of Debbarma et al (2018) who reported 29% anemia at childbirth among women from Imphal in India. The high prevalence of anemia in newborns could be explained by the fact that, the amount of iron transferred to the fetus by the pregnant woman depends on the amount of maternal iron available.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, endemic parasitic infections in these geographic areas, lifestyle and socio-economic conditions could also be associated with high prevalence of anemia (Ayano and Amentie, 2018). These results are similar to those of Debbarma et al (2018) who reported 29% anemia at childbirth among women from Imphal in India. The high prevalence of anemia in newborns could be explained by the fact that, the amount of iron transferred to the fetus by the pregnant woman depends on the amount of maternal iron available.…”
Section: Discussionsupporting
confidence: 76%